The Role of WTO in Food Safety During COVID-19 Pandemic - Azkhodjaeva, Rosa (Asian Pacific Journal of Environment and Cancer, 2020)
COVID-19 is a humanitarian crisis on a global scale. The virus continues to spread throughout the globe, placing health systems under unprecedented stress in the battle to save lives. The human scale of this tragedy is set to worsen as the virus spreads to lower income countries with weaker healthcare systems. COVID-19 could play a key role in developing serious collaps of the world economy. Worsening of the world economy is the main factor which affect to effectiveness of the international measures on poverty reduction of the world. Since COVID-19 period each country has priority to develop national and international Programs on food safety and develop/keep export programs in order to stabilize national economy and reduce poverty. It is important to keep and develop food producing system, increase possibility to export, improve international trade between countries. In this aspect the WTO could play a key role.